Kerukunan Antar Umat Beragama Keluarga Suku Dayak Ngaju di Palangka Raya - Normuslim Normuslim (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2018)
In the family of Dayak Ngaju ethnic group, their family members consist of the different religious adherent. Nevertheless, they live in harmony and peace to one another when in one roof without religious-based conflict. This research explores the dynamics of factors that facilitated the harmonious religious tolerance in this ethnic group. This research employs qualitative study with in-depth interview and observation to collecting data. In-depth interview and observation was conducted to families belong to Dayak Ngaju ethnic. The result of the research shows that three classifications attached to the characteristic of religious differences among their family members. 1) religious harmony is accommodate after serious conflict that leads to 'tolerant' attitude; 2) religious harmony is facilitated after medium conflict that leads to 'acceptance' attitude; 3) religious harmony is possible and maintained by all members of the family for they respect each other that leads to 'cooperation' attitude. This religious tolerance in the Dayak Ngaju family is possible because of three factors namely: the philosophy of huma betang, blood and family connection and the Kaharingan tradition as local wisdom.